Comparison between Palpation and Superficial Marking Techniques in Determining Infraorbital Foramen in Chinese Women - Lindawati, Lindawati; Soenggono, Arifin; Siswo, Hardi (Althea Medical Journal, 2015)
Background: Difficulties in determining infraorbital foramen were often found in anesthesia procedures, reconstruction surgery, acupuncture, and botox insertion. The most common technique used is palpation technique. However, there are some  disadvantages in this technique.The aim of this study was to  establish a new superficial marking technique to determine the position of infraorbital foramen by making a horizontal imaginary line from the top part of nose wings.Methods: This study was an analytical cross-sectional study conducted at the Faculty of Medicine, Universitas Padjadjaran in Jatinangor-Sumedang during the period of April to November 2012. A total of thirty Chinese female students were assessed to measure the mean distance between the inferior orbital margin to the infra orbital foramen and inferior orbital margin to horizontal imaginary line from the top part of nose wings. The differences were then checked using paired t-test.Results: There was a significance difference between the mean distance of the inferior orbital margin to the infra orbital foramen and the inferior orbital margin to the horizontal imaginary line from the top part of the nose wings on the right and left face of Chinese women with p<0.05 (p=0.000).Conclusion: Infra orbital foramen cannot be determined by using superficial marking technique in Chinese women.Keywords: Infra orbital foramen, palpation technique, superfacial marking techniqueDOI: 10.15850/amj.v2n1.427